Respostas

2014-05-14T22:05:48-03:00
(10.10.10) (-30.30) +4+1
1000 - 900 + 5
100+5
105
2014-05-14T22:12:33-03:00
( a.a.a) ( - 3a .3a) +( x.x) + ( y.y)   ,para a =10,×= 2 e y = 1

(a.a.a)( - 3a.3a) + (x.x) + (y.y) =

 (a)³    (-9a²)      +(x²)    +(y²) = 
(10)³ (-9(10²))    +(2²)    +(1²) =
(1000)(-9(100))  + 4 + 1 =
(1000)(-900) + 5
- 900.000 + 5 = -  899.995


ou

(a.a.a.)(-3a3a) +(x.x) + (y.y)
(10x10x10)(-3(10)3(10)) + (2x2) + (1x1) =
(1000)(-30(30)) + 4 + 1 =
(1000)(-900) + 5 =
- 900.000 + 5 = - 899.995